Terminology bank of nursing language - Tannure, Meire Chucre (2009)
This article presents the methodology which was used in the building of a terminology bank of specific nursing language. The process of extraction was described as well as the standardization of terms identified in ICU- adult patients’ clinical records, matching the extracted terms with the ones included in ICNP®-Version 1.0 and, classifying those not included in the 7 axes of classification. It is possible to identify terms that are used in nursing clinical practice and to build a terminology bank that can feed information systems which may aid nursing process stages implementation and CIPE® catalogues building.